What Matters Most for Engaging the Private Sector in Education : A Framework Paper - Baum, Donald; Lewis, Laura; Lusk-Stover, Oni; Patrinos, Harry (World Bank, Washington, DC, 2015)
This paper provides an overview of what matters most for engaging the private sector in basic education. In many countries, private schools educate a substantial and growing share of the student population. The goal of this paper is not to advocate for private schooling, but to outline the most effective evidence based policies that governments can use to orient these non-state providers toward promoting learning for all children and youth. Systems approach for better education results (SABER) engaging the private sector (EPS) builds upon the framework for effective service delivery outlined in the World Bank's World Development Report 2004, making services work for the poor, as well as in the World Bank's education sector strategy 2020, learning for all. To assist countries in improving their policy frameworks for private education, SABER EPS analyzes and benchmarks four policy goals that, according to the global evidence, can strengthen provider accountability and promote learning for all. These policy goals are: (1) encouraging innovation by providers; (2) holding schools accountable; (3) empowering all parents, students, and communities; and (4) promoting diversity of supply. Each of these policy goals is benchmarked across four common models of private service delivery: (a) independent private schools, (b) government funded private schools, (c) privately managed schools, and (d) voucher schools. In its country level application of the framework and tools, SABER EPS assesses only the modes of private delivery that already exist in each country.